Design of Electronic Remote Control System Based on Wireless Sensor - Li, Chunmei; Li, Bin; Shi, Guohong (International Journal of Online and Biomedical Engineering (iJOE), 2017)
A wireless remote sensing system based on wireless sensor network solution is proposed, to achieve the remote control of home appliances. The remote control system uses STM32F103 chip as the main controller of the smart home system, and applies the CC1110 radio frequency module as the communication node of the home wireless sensor network. Through the Simplici TI network protocol, these nodes together are put forward to form a small home LAN. Then, combining with GPRS wireless communication technology and Web Internet technology, these nodes to the remote server are collected. The results showed that through the user's mobile terminal access, it can form a wireless remote monitoring system. The conclusion is drawn that an intelligent home remote monitoring system based on wireless sensor network is feasible and it has good performances.